2023
DOI: 10.3390/sports11040091
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Training for Knee Osteoarthritis: A Narrative Review

Abstract: Knee osteoarthritis (OA) is the most common joint disease worldwide. Exercise therapy has been identified as a first-line treatment option in patients suffering from knee OA. High-intensity training (HIT) is an innovative exercise modality with potential in improving various disease-related outcomes. The purpose of this review is to explore the impact of HIT on knee OA symptoms and physical functioning. A comprehensive search of scientific electronic databases was conducted to identify articles on the effects … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 81 publications
(119 reference statements)
0
2
0
Order By: Relevance
“…Research has demonstrated that balance training can significantly improve patients’ balance ability and functional status, but its impact on muscle strength is not clearly evident due to limited studies ( 78 ). High-intensity interval training (HIIT) is considered a potentially beneficial exercise modality for improving symptoms and physical function in patients with KOA, including pain relief and functional enhancement ( 79 ). However, the superiority of HIIT compared to other exercise modalities still lacks clear evidence.…”
Section: Resultsmentioning
confidence: 99%
“…Research has demonstrated that balance training can significantly improve patients’ balance ability and functional status, but its impact on muscle strength is not clearly evident due to limited studies ( 78 ). High-intensity interval training (HIIT) is considered a potentially beneficial exercise modality for improving symptoms and physical function in patients with KOA, including pain relief and functional enhancement ( 79 ). However, the superiority of HIIT compared to other exercise modalities still lacks clear evidence.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the practice of "extreme" sports such as very long-distance running (only one patient practised endurance trail running in our population), which is very popular at the moment and is likely to be common practice among patients with OA in a few years' time, it is advisable to be cautious, and a specific case-control study could be useful given the limited number of people with OA currently practising these sports. However, clinical trials aimed at assessing the benefits of high-intensity training (HIT) have shown that HIT improves not only knee OA symptoms and physical functioning but also aerobic capacity, muscle strength, and quality of life with minimal or no adverse events [29].…”
Section: Discussionmentioning
confidence: 99%